2011
DOI: 10.1126/science.1206097
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Snf2-Related Nucleosome-Spacing Enzymes in Genome-Wide Nucleosome Organization

Abstract: The positioning of nucleosomes within the coding regions of eukaryotic genes is aligned with respect to transcriptional start sites. This organization is likely to influence many genetic processes, requiring access to the underlying DNA. Here we show that the combined action of Isw1 and Chd1 nucleosome spacing enzymes is required to maintain this organization. In the absence of these enzymes regular positioning of the majority of nucleosomes is lost. Exceptions include the region upstream of the promoter, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

37
319
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(370 citation statements)
references
References 30 publications
(31 reference statements)
37
319
1
2
Order By: Relevance
“…pattern requires whole-cell extract and ATP (13) and (ii) a combined knockout of several remodelers shows a clear phenotype in the average nucleosome pattern, whereas individual knockouts have mild effects (14). Given that both observations are at a physiological histone-DNA ratio, they can be rationalized kinetically only within the active SNG model: As previously pointed out (22), the intrinsic dynamics of nucleosomes, i.e., fluctuationinduced unbinding and diffusion along DNA, are too slow to equilibrate their positions on the relevant timescales of cell division or in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pattern requires whole-cell extract and ATP (13) and (ii) a combined knockout of several remodelers shows a clear phenotype in the average nucleosome pattern, whereas individual knockouts have mild effects (14). Given that both observations are at a physiological histone-DNA ratio, they can be rationalized kinetically only within the active SNG model: As previously pointed out (22), the intrinsic dynamics of nucleosomes, i.e., fluctuationinduced unbinding and diffusion along DNA, are too slow to equilibrate their positions on the relevant timescales of cell division or in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Within this framework, is there a single model that consistently explains all patterns? Second, recent experiments have shown in vitro (13) and in vivo (14) that the formation of the native nucleosome pattern requires the action of remodeling enzymes. Moreover, reduction of the histone-DNA ratio in vitro (13) or in vivo (15) does not lead to a concomitant increase in the typical nucleosome spacing, as would be expected for statistical positioning.…”
mentioning
confidence: 99%
“…Chd1 has been linked to various transcription-related processes, including regulation of nucleosome positioning at the 5′ end of transcribed genes (15,16), suppression of cryptic transcription (17,18), transcriptional elongation (17,19,20), and coupling of transcription with splicing (21). We have previously described Chd1 as a gene up-regulated in multiple mouse stem and progenitor cell types (22,23).…”
mentioning
confidence: 99%
“…The in vitro nucleosome maps were generated by reconstituting nucleosomes on yeast genomic DNA, in the presence or absence of trans-acting factors, represented by cell extracts or ATP-dependent chromatin remodelers (Kaplan et al 2009;Zhang et al 2009Zhang et al , 2011b. Such experiments revealed that trans-acting factors, rather than the DNA sequence preferences of nucleosomes (Zhang et al 2009(Zhang et al , 2011bGkikopoulos et al 2011;Hughes et al 2012;Yen et al 2012), mainly underlie the characteristic nucleosome array downstream from TSSs. This stands in contrast to the regulatory nucleosome-depleted regions upstream of TSSs, which were found to be intrinsically unfavorable to nucleosome formation (Kaplan et al 2009;Zhang et al 2009).…”
mentioning
confidence: 99%